A quantitative assessment of atmospheric emissions and spatial distribution of trace elements from natural sources in China. (April 2020) - Wu, Yiming; Lin, Shumin; Tian, Hezhong; Zhang, Kai; Wang, Yifei; Sun, Bowen; Liu, Xiangyang; Liu, Kaiyun; Xue, Yifeng; Hao, Jiming; Liu, Huanjia; Liu, Shuhan; et al.
Abstract: Natural sources, such as soil and wind-erosion dust (SWD), biomass open burning (BOB), sea salt spray (SSAS) and biogenic source (BIO), are major contributors to atmospheric emissions of trace elements (TEs) globally. In this study, we used a comprehensive approach to account for area-, production- and biofuel consumption-based emission factor calculation methods, and thus developed an integrated high-resolution emission inventory for 15 types of TEs (As, B, Cd, Co, Cr, Cu, Hg, Mn, Mo, Ni, Pb, Sb, Se, V and Zn) originated from natural sources in China for the year 2015. The results show that national emissions of TEs in 2015 range from 7.45 tons (Hg) to 1, 400 tons (Zn) except for the extremely high emissions of Mn (10, 677 tons). SWD and BIO are identified as the top two source contributors, accounting for approximately 67.7% and 26.1% of the total emissions, respectively. Absolute emissions of TEs from natural sources are high in the Xinjiang, Inner Mongolia and Tibet autonomous regions with large areas of bare soil and desert. However, emission intensity of TEs per unit area in the Southern provinces of China is higher than those in Northern China and Southwestern China, with the Yunnan and Sichuan provinces displaying the highest emission intensity. Our results suggest that controlling SWD can play a significant role in reducing fugitive particulate matter and the associated emissions of TEs from natural sources in China; and desertification control is particularly critical in the Northwest provinces where the majority of deserts are located. Graphical abstract: Image 1 Highlights: Emission of Mn (10, 677t) from natural sources ranks 1st in 15 trace elements in China. Emissions of other elements in 2015 range from 7.45 tons (Hg) to 1, 400 tons (Zn). Soil & wind-erosion dust and biogenic are identified as the two biggest contributors. Soil & wind-erosion dust shared over 95% of total emission of Cr, Co, As, Mn and V. Emission intensity per unit land is higher in Southern than that in Northern provinces.